Low-density SNP markers with high prediction accuracy of genomic selection for bacterial wilt resistance in tomato - Yeon, Jeyun; Le, Ngoc Thi; Heo, Jaehun; Sim, Sung-Chur (Frontiers in Plant Science, 2024)
Bacterial wilt (BW) is a soil-borne disease leading to severe damages in tomato. Host resistance against BW is considered polygenic and effective to control this destructive disease. In this study, genomic selection (GS), which is a promising breeding strategy to improve quantitative traits, was investigated for BW resistance. Two tomato collections, TGC1 (n=162) and TGC2 (n=191) were used as training populations. Disease severity was assessed using three seedling assays in each population and the best linear unbiased prediction (BLUP) values were obtained. The 31,142 SNP data were generated using the 51K Axiom arrayTM in the training populations. With these data, six GS models were trained to predict genomic estimated breeding values (GEBVs) in three populations (TGC1, TGC2, and combined). The parametric models, Bayesian LASSO and RR-BLUP resulted in higher levels of prediction accuracy compared to all the non-parametric models (RKHS, SVM, random forest) in two training populations. To identify low-density markers, two subsets of 1,557 SNPs were filtered based on marker effects (Bayesian LASSO) and variable importance values (random forest) in the combined population. An additional subset was generated using 1,357 SNPs from a genome-wide association study. These subsets showed the prediction accuracies of 0.699 to 0.756 in Bayesian LASSO and 0.670 to 0.682 in random forest, which were higher relative to the 31,142 SNPs (0.625 and 0.614). Moreover, high prediction accuracies (0.743 and 0.702) were found with a common set of 135 SNPs derived from the three subsets. The resulting low-density SNPs will be useful to develop a cost-effective GS strategy for BW resistance in tomato breeding programs.